E-Learning Adoption in Open Learning Programs: A Case Study of Public and Private Universities in Jeddah City - Al-Taweel, Sadik Ali; Al-Abdali, Abdurahman H.; Al-Fuhaidi, Belal (Foundation of Computer Science (FCS), 2019)
This research was carried out in three public and private universities in Jeddah City, Kingdom of Saudi Arabia. These universities use electronic materials in their programs. The main objective of this paper was to assess the adoption of elearning in Saudi universities. A survey was conducted on elearning activities given to students throughout their study. A structured questionnaire was designed and distributed to 154 students from the selected universities. Based on data analysis, the main findings showed that students are inadequately qualified to adopt e-learning technology in their learning life. There is an obvious weakness of students in learning through uses of technology devices. They have deep belief in traditional learning. Although the universities in Saudi Arabia have good infrastructure and funding for more projects to adopt e-learning technology and encourage students to use it, this did not work well to support and encourage students to be more familiar with and interested in e-learning techniques. This is perhaps because of the absence of legislation that may regulate the adoption process of elearning among students. Most of the facilities that were offered by universities did not convince the students to be involved in e-learning technology. The factors that negatively affect adopting e-learning among students are the lack of computer skills, low bandwidth connectivity of the internet and high cost of more bandwidth.